2012
DOI: 10.1007/s00125-012-2644-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin sensitivity by serine/threonine phosphorylation of insulin receptor substrate proteins IRS1 and IRS2

Abstract: The insulin receptor substrate proteins IRS1 and IRS2 are key targets of the insulin receptor tyrosine kinase and are required for hormonal control of metabolism. Tissues from insulinresistant and diabetic humans exhibit defects in IRS-dependent signalling, implicating their dysregulation in the initiation and progression of metabolic disease. However, IRS1 and IRS2 are regulated through a complex mechanism involving phosphorylation of >50 serine/threonine residues (S/T) within their long, unstructured tail re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
703
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 847 publications
(733 citation statements)
references
References 177 publications
(303 reference statements)
15
703
2
13
Order By: Relevance
“…To test whether Hh activates Igf signaling, we monitored the phosphorylation of insulin receptor substrate 1 (Irs1) at S632/635 (equivalent of S636/639 in human IRS1), which is stimulated by insulin or Igf signaling (31). In keeping with the maximal induction of Igf2 at 48 h, PM notably increased both total-and phospho-Irs1 at 48 and 72 h (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…To test whether Hh activates Igf signaling, we monitored the phosphorylation of insulin receptor substrate 1 (Irs1) at S632/635 (equivalent of S636/639 in human IRS1), which is stimulated by insulin or Igf signaling (31). In keeping with the maximal induction of Igf2 at 48 h, PM notably increased both total-and phospho-Irs1 at 48 and 72 h (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…FSH Activates PP1c␤ to Dephosphorylate Inhibitory IRS1 Ser/ Thr Residues-Extensive research has attributed the development of insulin resistance and type II diabetes to inhibitory Ser/Thr phosphorylations on IRS1 that impair both tyrosine phosphorylation of IRS1 by the insulin receptor and activation of downstream targets like PI3K (44,58). As a result, we asked whether FSH could be stimulating the dephosphorylation of inhibitory Ser/Thr residues within IRS1 to sensitize IRS1 to the tyrosine kinase activity of the IGF-1R.…”
Section: Fsh and Igf-1 Do Not Intersect Through A Tyrosinementioning
confidence: 99%
“…Indeed, S6K1 participates in insulinmediated cell growth but-like mTORC1-also operates negative feedback loops at various levels of regulation. For example, several studies have shown that both mTORC1 and/or S6K1 phosphorylate specific serine residues on IRS proteins [6,7]. Moreover, some of these IRS-1 sites, notably Ser 1101 and Ser 636, were differentially regulated by mTOR and S6K1 [8,9].…”
Section: Introductionmentioning
confidence: 99%